Alterations in the β Flap and β′ Dock Domains of the RNA Polymerase Abolish NusA-Mediated Feedback Regulation of the metY-nusA-infB Operon - Bylund, Göran O. (American Society for Microbiology, 2011)
The RimM protein in Escherichia coli is important for the in vivo maturation of 30S ribosomal subunits and a ΔrimM mutant grows poorly due to assembly and translational defects. These deficiencies are suppressed partially by mutations that increase the synthesis of another assembly protein, RbfA, encoded by the metY-nusA-infB operon. Among these suppressors are mutations in nusA that impair the NusA-mediated negative-feedback regulation at internal intrinsic transcriptional terminators of the metY-nusA-infB operon. We describe here the isolation of two new mutations, one in rpoB and one in rpoC (encoding the β and β′ subunits of the RNA polymerase, respectively), that increase the synthesis of RbfA by preventing NusA from stimulating termination at the internal intrinsic transcriptional terminators of the metY-nusA-infB operon. The rpoB2063 mutation changed the isoleucine in position 905 of the β flap-tip helix to a serine, while the rpoC2064 mutation duplicated positions 415 to 416 (valine-isoleucine) at the base of the β′ dock domain. These findings support previously published in vitro results, which have suggested that the β flap-tip helix and β′ dock domain at either side of the RNA exit tunnel mediate the binding to NusA during transcriptional pausing and termination.